The skeptical environmentalist : measuring the real state of the world - Lomborg, Bjorn (Cambridge University Press, 2001)
Bjørn Lomborg, a former member of Greenpeace, challenges widely held beliefs that the world environmental situation is getting worse and worse in his new book, The Skeptical Environmentalist. Using statistical information from internationally recognized research institutes, Lomborg systematically examines a range of major environmental issues that feature prominently in headline news around the world, including pollution, biodiversity, fear of chemicals, and the greenhouse effect, and documents that the world has actually improved. He supports his arguments with over 2500 footnotes, allowing readers to check his sources. Lomborg criticizes the way many environmental organizations make selective and misleading use of scientific evidence and argues that we are making decisions about the use of our limited resources based on inaccurate or incomplete information. Concluding that there are more reasons for optimism than pessimism, he stresses the need for clear-headed prioritization of resources to tackle real, not imagined, problems. The Skeptical Environmentalist offers readers a non-partisan evaluation that serves as a useful corrective to the more alarmist accounts favored by campaign groups and the media. Bjørn Lomborg is an associate professor of statistics in the Department of Political Science at the University of Aarhus. When he started to investigate the statistics behind the current gloomy view of the environment, he was genuinely surprised. He published four lengthy articles in the leading Danish newspaper, including statistics documenting an ever-improving world, and unleashed the biggest post-war debate with more than 400 articles in all the major papers. Since then, Lomborg has been a frequent participant in the European debate on environmentalism on television, radio, and in newspapers.
Keywords: ekologie; environmentální vědy; Environment; životní prostředí; Ecology